Rare Contents of an Internal Hernia through a Defect of the Broad Ligament of the Uterus - Masafumi Takahashi; Masanori Yoshimitsu; Takuya Yano; Hitoshi Idani; Shigehiro Shiozaki; Masazumi Okajima (Case Reports in Surgery)
Herniation through a defect of the uterine broad ligament is a rare internal hernia that is difficult to diagnose definitively. Common hernia contents contain ileal loops. Herein, we report a rare case of internal herniation of both the ileum and fallopian tube through a defect of the broad ligament. A 52-year-old woman presented to our hospital with suprapubic pain and vomiting. She had a history of bowel obstruction following cesarean section. On abdominopelvic computed tomography, we suspected a closed-loop obstruction associated with bowel herniation in the right broad ligament. However, we could not identify an area of poor enhancement adjacent to distended small intestines. Emergency laparoscopic exploration revealed a viable ileal loop and incarcerated organ. Therefore, we switched to laparotomy that revealed the right fallopian tube as the ischemic organ. We reduced the hernia, resected necrotic right fallopian tube, and closed the defect of the broad ligament. The patient had an uneventful postoperative course. Rare hernia contents might complicate preoperative clinical diagnosis. Laparoscopy is useful for establishing a definitive diagnosis and treating broad ligament hernias.